2002
DOI: 10.1002/cne.10276
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of myelinated and unmyelinated nerve fibers and their possible role in blood flow control in crotaline snake infrared receptor organs

Abstract: We used transmission electron microscopic montages to examine the composition of nerve bundles serving the infrared pit organs of two species of crotaline snakes, Agkistrodon blomhoffii and A. brevicaudus. In the three main bundles, the myelinated fibers totaled 2,200-3,700, and unmyelinated fibers 2,400. We also discovered for the first time two accessory bundles composed almost entirely of unmyelinated fibers running alongside the main bundles, containing an average total of 3,300 unmyelinated fibers vs. an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Even though TNMs in the epithelium are formed by different nerve branches, the diameters of all TNMs are very similar, compatible with the measurements of earlier reports (Bullock and Fox, ; Terashima et al, ). Furthermore, the number of labeled TNMs in our study of ∼5,000 for a pit area of ∼6 mm 2 was comparable to the number of TNMs (Hisajima et al, ) and the number of infrared‐sensitive cell bodies in the trigeminal ganglia reported for Gloydius brevicaudus (Kishida et al, ) as well as for Crotalus horridus (Bullock and Fox, ) after correction for noninfrared‐sensitive C‐fibers in the latter study. Although the peripheral innervation of the pit membrane by V2s and V2d is separated, there is considerable intermingling of the cell bodies in the maxillomandibular ganglionic complex, compatible with the inference from previous studies (Kishida et al, ; Terashima and Liang, ).…”
Section: Discussionsupporting
confidence: 88%
“…Even though TNMs in the epithelium are formed by different nerve branches, the diameters of all TNMs are very similar, compatible with the measurements of earlier reports (Bullock and Fox, ; Terashima et al, ). Furthermore, the number of labeled TNMs in our study of ∼5,000 for a pit area of ∼6 mm 2 was comparable to the number of TNMs (Hisajima et al, ) and the number of infrared‐sensitive cell bodies in the trigeminal ganglia reported for Gloydius brevicaudus (Kishida et al, ) as well as for Crotalus horridus (Bullock and Fox, ) after correction for noninfrared‐sensitive C‐fibers in the latter study. Although the peripheral innervation of the pit membrane by V2s and V2d is separated, there is considerable intermingling of the cell bodies in the maxillomandibular ganglionic complex, compatible with the inference from previous studies (Kishida et al, ; Terashima and Liang, ).…”
Section: Discussionsupporting
confidence: 88%
“…It is also possible that DMSO affects the IR response via the pit vasculature in crotaline snakes. However, the potent vasodilator CGRP and substance P (McCulloch et al, 1986) do not affect the IR response in this snake (Terashima and Moon, 2003), although the coexistence of CGRP and substance P immunoreactivity has been reported in autonomic/c-fiber nerves in the pit membrane (Kadota et al, 1997;Hisajima et al, 2002). It is interesting, therefore, that all the effective vasodilators (EtOH, DMSO, and NO) increased the IR response, while a vasoconstrictor (ET-1) decreased it.…”
Section: Discussionmentioning
confidence: 92%
“…The enhanced visual acuity gained from maintaining the eye at an elevated temperature provides a distinct reaction time advantage over their highly active, but ectothermic prey. On the other hand, consider an ectothermic predator that senses heat; the pit organ of the pit viper is a highly evolved infrared sensing tissue, consisting of a thin membranous tissue dense in mitochondria, myelinated and unmyelinated nerves, and a high vascularity (Goris et al, 2007; Hisajima et al, 2002). The latter has been argued to aid in providing rapid blood flow to help reduce after images formed during heat sensing (Goris et al, 2007).…”
Section: Introductionmentioning
confidence: 99%